Accuracy of non-invasive hemoglobin monitoring by pulse CO-oximeter during hepatectomy in living liver donors (Annals of Medical Research, 2021)
Aim: To evaluate the accuracy and agreement of the measurements made with the Masimo Rad7 device in living donor hepatectomy (LDH).Materials and Methods: A total of 63 living liver donors (LLDs) with ASA I-II scores who scheduled for LDH were included in the study. The Masimo noninvasive measurement probe was inserted to measure SpHb (mg/dL), pleth variability index (PVI, %) and perfusion index (PI,%). Heart rate, mean artery pressure, SpO2, body temperature, BIS, PVI, SpHb, and PI were recorded as basal, after anesthesia induction, post-intubation, post-intubation plus 5 min, 10 min, and plus 1, 2, 3, 4, 5, 6 and 7h. In addition blood samples were collected for laboratory hemoglobin (Hblab) before the surgery incision and after the surgical procedure, and the values were recorded simultaneously with the other values.Results: Fifty-five LLDs age between 18 and 55 years were assessed. The mean PI value increased in all measurements compared to baseline, and it was statistically significant at the 5th minute (p
Keywords: Hepatectomy; living liver donors; non-invasive hemoglobin monitoring; pulse CO-oximeter